Give your heart to the hawks [large type] : a tribute to the mountain men - Blevins, Winfred (Wheeler Publishing, a part of Gale, a Cengage Company, 2018)
For more than thirty years, mountain men explored the Great American West, opening the gates of the mountains for the wagon trains of pioneers that followed. Win Blevins' poetic tribute to their incredible adventures includes, among many, the stories of John Colter, who, in 1808, without clothing, weapons, or food, escaped captivity by the Blackfeet and traveled 250 miles on foot to Fort Lisa; And Hugh Glass, who in 1823 was mauled by a grizzly, left for dead by his trapper companions, and crawled 300 miles to Fort Kiowa on the Missouri.